2011
DOI: 10.3109/10826084.2011.580169
|View full text |Cite
|
Sign up to set email alerts
|

Global Issues in Volatile Substance Misuse

Abstract: This special issue of Substance Use & Misuse addresses the public health issue of volatile substance misuse (VSM), the inhalation of gases or vapors for psychoactive effects, assessing the similarities and differences in the products misused, patterns, prevalence, etiologies, and impacts of VSM by examining it through sociocultural epidemiology, neuroscience, and interventions research. The Canadian, US, and Australian guest editors contend that, when compared with other drugs used at a similar prevalence, VSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 16 publications
0
22
0
2
Order By: Relevance
“…In other populations, inhalants have been linked to cognitive and neurological impairment, sudden sniffing death syndrome due to cardiac arrhythmia, renal, pulmonary and teratogenic effects [58,66,68]. Additionally, evidence exists of psychological and physical dependence among volatile solvent users [30,69].…”
Section: Discussionmentioning
confidence: 99%
“…In other populations, inhalants have been linked to cognitive and neurological impairment, sudden sniffing death syndrome due to cardiac arrhythmia, renal, pulmonary and teratogenic effects [58,66,68]. Additionally, evidence exists of psychological and physical dependence among volatile solvent users [30,69].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is also supported by one of our previous studies that demonstrated that d -serine, also a selective co-agonist at the glycine binding site of NMDA receptors, reversed locomotor hyperactivity, motor incoordination, and learning impairment induced by toluene administration in rats (Lo et al , 2009). Indeed, the neurobehavioral profiles of toluene including biphasic effect on locomotor activity (Riegel and French, 1999; Riegel et al , 2003; Chan et al , 2004; Dell et al , 2011), ataxia (Lo et al , 2009), and learning impairments (Lo et al , 2009; Win-Shwe et al , 2010; Huerta-Rivas et al , 2012) overlap those of NMDA receptor antagonists, such as phencyclidine (PCP) and ketamine. Sarcosine and another GlyT1 inhibitor, N -(3-[4’-fluorophenyl]-3-[4’-phenylphenoxy]propyl)sarcosine (NFPS), have been reported to antagonize the effects of NMDA receptor channel blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile substance abuse is a dangerous behavior that has been documented throughout the world [13,43]. Within just the United States, a recent National Survey on Drug Use and Health estimates that more than 22 million Americans twelve years of age and older have abused volatile substances at least once in their lifetimes [48].…”
Section: Introductionmentioning
confidence: 99%